Syaikh Ahmad Khatib Al-Minakabawi: Mahaguru Ulama Nusantara di Makkah dan Respon Ilmiah Terhadap Permasalahan di Nusantara Abad Ke 19-20 M - Dzulkifli Hadi Imawan; Muhammad Faiz (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2021)
Abstract: This study explains about Shaykh Ahmad Khatib al-Minakabawi and his response to the problems that occurred in the archipelago in the 19th-20th centuries AD. This study aims to analyze the teaching of Shaykh Ahmad Khatib to reformers in the archipelago who had studied with him in Mecca as well as scientific works that were a response to problems in the archipelago in the 19-20 century AD. The research method used studies literature, namely a qualitative descriptive study with historical analysis to examine data on the contribution of Shaykh Ahmad Khatib. The results of this study explain that Shaykh Ahmad Khatib is a professor of the Nusantara ulema in Mecca who has succeeded in guiding them to become reformers in the archipelago and has great attention to the problems that occur in the archipelago which he responds with scientific works to explain and straighten these problems.